2021
DOI: 10.3390/agriculture11090867
|View full text |Cite
|
Sign up to set email alerts
|

Biopesticide Evaluation from Lab to Greenhouse Scale of Essential Oils Used against Macrosiphum euphorbiae

Abstract: Aphids are recognized as a major threat to economically important crops. Their control is predominantly based on synthetic insecticides that are detrimental to human health and the environment. Botanical pesticides based on essential oils (EOs) are a promising alternative. In this study, the entomotoxicity of green anise and fennel EO fumigation was tested on the potato aphid Macrosiphum euphorbiae. Three different settings of increasing scale were considered (leaflet, whole plant and greenhouse) to appraise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Indeed, EOs jeopardize the success of natural regulation by direct or indirect effects on natural enemy fitness. Using EOs for plant protection would require to carefully study the benefits (toxicity on pests) and risks (effects on natural enemies and phytotoxicity) (Dunan et al, 2021). This study also sets out possibilities for biocontrol programs that integrate semiochemicals to optimize the efficiency of egg parasitoids in agroecosystems (Wajnberg and Colazza, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, EOs jeopardize the success of natural regulation by direct or indirect effects on natural enemy fitness. Using EOs for plant protection would require to carefully study the benefits (toxicity on pests) and risks (effects on natural enemies and phytotoxicity) (Dunan et al, 2021). This study also sets out possibilities for biocontrol programs that integrate semiochemicals to optimize the efficiency of egg parasitoids in agroecosystems (Wajnberg and Colazza, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to explore the Lamiaceae family by including two common aromatic plants: Basil ( Ocimum basilicum , Lamiaceae) and Oregano ( Origanum vulgare , Lamiaceae) (Ikbal and Pavela, 2019). We diversified plant families by including Asteraceae: Mugwort ( Artemisia vulgaris , Asteraceae) (Wang et al, 2006) and three Apiaceae: Coriander ( Coriandrum sativum , Apiaceae) (Khedr et al, 2013), Green anise ( Pimpinella anisum , Apiaceae) and Fennel ( Foeniculum vulgare , Apiaceae) (Dunan et al, 2021). All EOs were obtained from Esperis s.p.a..…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies have focused on the EOs bioactivity toward greenhouse insect pests (Campolo et al 2017;Dunan et al 2021;Sciortino et al 2021;Tortorici et al 2022), limited knowledge on EOs non-target effect toward beneficial arthropods has been produced. Earlier laboratory studies assessed the non-target impact of Citrus spp., Mentha pulegium L. and garlic (Allium sativum L.) EOs on N. tenuis in terms of acute toxicity and sublethal effects (Papadimitriou et al 2019;Soares et al 2019;Campolo et al 2020b;Ricupero et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, this change in scale might have tremendous effects on efficacy. In this context, Dunan et al, in a series of experiments on an increasing scale, reported that botanical pesticides based on essential oils (EOs) could be promising alternatives to combat aphids [5]. In particular, the entomotoxicity of green anise and fennel EO fumigation was tested on the potato aphid, Macrosiphum euphorbiae.…”
mentioning
confidence: 99%